Corporate venturing: Insights from actual performance - Kuratko,Donald F.; Covin,Jeffrey G.; Garrett,Robert (Business Horizons, 2009)
Corporate innovation and the entrepreneurial strategies on which it is based are key challenges at the forefront of executive concerns. In order to establish some factual foundations amid the popular “folklore” that surrounds corporate innovation today, this study examines the actual factors that influence internal corporate venturing within the realm of a corporate entrepreneurship strategy. Data were collected from 145 internal corporate ventures (early-stage ventures, middle-stage ventures, and established-stage ventures) operating in 72 firms headquartered in the mid-western United States. The results of this study are summarized and offer insights on some of the key correlates of corporate venturing performance.
Keywords: Strategy & Entrepreneurship